Collins primary focus grammar and punctuation: introductory teacher's guide - Fidge, Louis; Lindsey, Sarah (Collins Educational London, 2011)
Collins Primary Focus: Grammar and Punctuation Guide contains teaching notes for every unit: learning objectives, matched to APP, definitions, background information, shared, guided and independent writing activities, group and pair work ideas, speaking and listening activities, support and extension worksheets.